Enzymatic Interesterification of Palm Stearin and Sardine oil to Produce Margarine-fat - Pudji Hastuti; Tyas Utami (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
Enzymatic interesterification of Palm Stearin (PS) and Sardine Oil (SO) as source of Eicosa Pentaenoic Acid (EPA) and Docosa Hexaenoic Acid (DHA) have been of interest to modify the physical properties of the triglyceride. An attempt to enzymatic-restructure PS and SO to form Structured Lipid (SL) which is suitable for margarine was investigated using immobilized lipase from Rhizomucor miehei and that from Candida antartica. The effect of reaction time course, ratio of PS/SO and ratio of enzyme/substrate were studied in the present study. At the end of interesterification, the enzyme was filtered from the reaction mixture through a filter paper. The Solid Fat Index (SFI) was determined by dillatometry. The Slip Melting Point (SMP) was determined by capillary tube method. Both of interesterification catalyzed by immobilized sn 1,3 specific lipase from R.miehei,and non specific lipase from C.antartica were found to decrease the SFI value at 10; 21.1 and 33.30C. The SMP value was decrease from 58-500C to 37-390C. The change of these parameters were slightly faster in the reaction which catalyzed by lipase from R miehei than lipase from C.antartica . The more the utilization of the enzyme the faster the change were occurred, especially the increase of enzyme utilization from 2.5% to 5%, which decrease the SFI value at 33,30C. The decrease of the PS/SO ratio resulted in the decrease of SFI and SMP values. It was found that the most suitable SFI and SMP value for margarine fat is the SL formed by carrying out the enzymatic-interesterification of PS/SO with the ratio of 40/60 using enzyme 2.5% of the total fat, for 8 hours at 600C. Key words : Palm stearin, sardine oil, enzymatic-interesterification, solid fat index and slip melting point